Relationship Between Oxidative Stress Markers and Endothelin-1 Levels in Newborns of Different Gestational Ages - Stefanov, Gospodin; Briyal, Seema; Pais, Gwendolyn; Puppala, Bhagya; Gulati, Anil (Frontiers in Pediatrics, 2020)
Oxidative stress results from excessive reactive oxygen species formation and/or inadequate antioxidant defense. Premature and critically ill infants are especially susceptible due to an immature intrinsic antioxidant system that cannot fully compensate for a free radical load. Oxidative stress is also associated with endothelial dysfunction and alterations in Endothelin-1 (ET-1) signaling pathways. However, the effects of the complex interaction between oxidative stress and ET-1 in newborns are not well understood. The objective of this pilot study was to determine the relationship between levels of common oxidative stress biomarkers (glutathione [GSH], malondialdehyde [MDA]) and ET-1 in newborns of different gestational ages. In a level IV NICU, 63 neonates were prospectively enrolled and divided into groups based on gestational age at birth: Early Preterm (24 0/7 to 30 6/7 weeks), Late Preterm (31 0/7 to 36 6/7 weeks), and Term (37 0/7 to 42 weeks). Umbilical cord (1.5mL) and 24(±4) hours of life (24h) (1mL) blood samples were collected for GSH, MDA and ET-1 analyses. GSH, MDA, and ET-1 were determined using established methodology. Mean cord MDA levels for all age groups, Early Preterm (2.93±0.08pg/ml), Late Preterm (2.73±0.15pg/ml), and Term (2.92±0.13pg/ml), were significantly higher than those at 24h of life (p<0.001). Mean cord ET-1 levels were significantly higher than 24h samples in both Early and Late Preterm groups (p<0.05). Cord and 24h ET-1 levels did not correlate with MDA and GSH levels at birth (r2=0.03, p>0.05 and r2=0.001, p>0.05; respectively) or 24h of life (r2=0.001, p>0.05 and r2=0.03, p>0.05; respectively). Preterm neonates exposed to prenatal corticosteroids (1.87±0.31pg/ml) had lower cord MDA levels than non-exposed neonates (2.85±0.12pg/ml) (p<0.05). Both cord and 24h OS markers were significantly higher in neonates treated with oxygen therapy (p<0.005 and p<0.05; respectively) than those who did not receive supplemental oxygen. Oxidative stress markers (MDA and GSH) and ET-1 levels act independently. MDA is higher in cord blood than at 24 hours of life regardless of gestational age. Oxygen therapy increases MDA and GSH levels. Prenatal steroids may reduce oxidative stress injury directly via the lipid peroxidation pathway and/or indirectly by decreasing neonatal morbidities, such as respiratory distress syndrome.